Characterization of endogenous promoters of GapC1 and GS for recombinant protein expression in Phaeodactylum tricornutum. Issue 5 (25th October 2021) - Erdene‐Ochir, Erdenedolgor; Shin, Bok‐Kyu; Huda, Md Nazmul; Lee, Eun Ha; Song, Dae‐Geun; Jung, Choonkyun; Pan, Cheol‐Ho
Abstract: Although diatoms have been utilized as a cellular factory to produce biopharmaceuticals, recombinant proteins, and biofuels, only a few numbers of gene promoters are available. Therefore, the development of novel endogenous promoters is essential for the production of a range of bioactive substances. Here, we characterized the activities of endogenous promoters glyceraldehyde ‐ 3 ‐ phosphate dehydrogenase ( GapC1 ) and glutamine synthetase ( GS ) of Phaeodactylum tricornutum using green fluorescent protein (GFP) under different culture conditions. Compared with the widely used fucoxanthin chlorophyll‐binding protein A ( fcpA ) promoter, the GS promoter constitutively drove the expression of GFP throughout all growth phases of P .  tricornutum, regardless of culture conditions. Additionally, the GFP level driven by the GapC1 promoter was the highest at the log phase, similar to the fcpA promoter, and increased light and nitrogen‐starvation conditions reduced GFP levels by inhibiting promoter activity. These results suggested that the GS promoter could be utilized as a strong endogenous promoter for the genetic engineering of P .  tricornutum . Abstract : The endogenous promoter of glutamine synthetase (GS) strongly drove green fluorescent protein (GFP) expression during all growth phases of the diatom Phaeodactylum tricornutum and under multiple growth conditions, including nitrogen starvation and increased light intensity. These results indicate that the GS promoter could be utilized as a strong promoter for the genetic engineering of P. tricornutum.